Students’ Perception of Google Classroom and Microsoft Teams Using TAM-Based Constructs - Rungkaew, Titirut (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examined undergraduate students’ perceptions of Google Classroom and Microsoft Teams using five constructs of the Technology Acceptance Model (TAM): Perceived Usefulness (PU), Perceived Ease of Use (PEU), Perceived Enjoyment (PE), Task-Technology Fit (TTF), and Perceived Resources (PR). A total of 300 students enrolled in a Thai university participated, with each course section using one of the two platforms for at least three weeks prior to data collection. Research design, data and methodology: A quantitative, cross-sectional survey design was employed. Data were analyzed using descriptive statistics, reliability analysis, and independent samples t-tests to compare perceptions between the platforms. Results: Students reported generally positive perceptions toward both LMSs, with all means falling within the “agree” range. Although Microsoft Teams showed slightly higher descriptive ratings, independent samples t-tests indicated no statistically significant differences across all constructs. Independent samples t-tests indicated no statistically significant differences between platforms across all five constructs (p > .05). Conclusions: The findings suggest that both platforms are perceived as similarly useful, intuitive, enjoyable, and adequately supported for academic tasks. Institutional decisions regarding LMS adoption may therefore rely on practical considerations such as integration, cost, or technical support rather than differences in student perception. The findings highlight that LMS adoption decisions in Thai university may not hinge on platform choice alone but on institutional support, instructional practices, and contextual readiness.